Characteristics of Educational Education Rate in Children with DHF - Riada Marenny Pasaribu (Science Midwifery, 2022)
The erythrocyte sedimentation rate (ED) is the rate at which red blood cells settle in a special examination tube in mm/hour (read: millimeters per hour). On examination, the LED will show a high, normal, or low LED. A high erythrocyte sedimentation rate means that the rate of red blood cell deposition is faster than normal. The red blood cells in the body are evenly distributed throughout the blood plasma because the blood continues to flow. showed that from 20 patients, 8 people were diagnosed with DHF with a range of LED counts of 22-35 mm/hour.2. And 12 people who were not diagnosed with DHF with a range of 7-20 mm/hour LED count.3. It is expected to always carry out LED checks on children with DHF using the Westergreen method because the results are more accurate and do not require large funds.